Motivation to work: A case study of problems faced by factory workers / Tang Chung kim - Tang , Chung kim (1983)
This graduation exercise will touch on a number of topics in the field of industrial sociology. Specifically, it is about the factory workers - the people who make the industrial machinery work. A summary of the area to be studied is as follows: Chapter one will discuss about the criteria in choosing a factory and the use of the various data collecting methods. Chapter two will look into the various aspects of the factory (such as location, size, history and capital), the production process and the actual working conditions. A comparison of the minimum legal conditions and conditions in the factory will also be made. The general wage structure will be found in this chapter also. The socio-economic characteristics of the sample will be central topic in chapter three. The method of choosing the sample will be shown. Besides that, the worker attitudes, wages and socio-economic characteristics are other main topics of discussion in this chapter. Lastly, a typical factory worker ' s monthly budget will also be described. Chapter four is totally devoted to the totally unions, the workers' sabotage tactics and the management ' s control strategies. Finally, the conclusion touches on the scope, the major findings and the weakness s of the study, Recommendations Me. Also put forward by the author.